DEK-AFF2 fusion-associated papillary squamous cell carcinoma of the sinonasal tract – A systematic review. - Shunmugavelu, Dr. Karthik; Leo , Antowin; Nathiyal, Dr. Velusamy (Student’s Journal of Health Research Africa, 2026)
Background Papillary squamous cell carcinoma of the sinonasal tract is an uncommon malignancy with diverse histopathological features and poorly understood molecular drivers. Recently, a recurrent DEK-AFF2 gene fusion has been reported in a subset of sinonasal squamous cell carcinomas displaying papillary architecture and deceptively bland morphology. The objective of this systematic review was to evaluate current evidence regarding the clinicopathological and molecular association between DEK-AFF2 fusion and papillary squamous cell carcinoma of the sinonasal tract. Methods A systematic literature search was conducted following PRISMA guidelines. Electronic databases, including MEDLINE, PubMed, Scopus, Embase, Web of Science, and LILACS, were searched for studies published between 2020 and 2024. Eligibility criteria included original research articles reporting clinicopathological or molecular characteristics of sinonasal papillary squamous cell carcinoma associated with DEK-AFF2 fusion. Data items extracted included author, year, study design, molecular findings, and clinical outcomes. Study quality was evaluated using the STROBE checklist. A qualitative synthesis of eligible studies was performed. Results Four studies met the inclusion criteria. The reviewed literature consistently demonstrated that DEK-AFF2 fusion defines a distinct subset of sinonasal squamous cell carcinoma characterized by papillary growth patterns, bland cytological features, and molecular alterations distinct from conventional sinonasal papillomas or HPV-associated carcinomas. These tumors frequently lacked EGFR or KRAS mutations and typically tested negative for transcriptionally active human papillomavirus. Despite their deceptively low-grade morphology, several studies reported local recurrence and aggressive clinical behavior. Conclusion DEK-AFF2 fusion-associated papillary squamous cell carcinoma represents an emerging molecular subtype of sinonasal carcinoma with unique histopathological and genetic characteristics. Recognition of this entity is important for accurate diagnosis and clinical management. Future research Further multi-institutional studies integrating genomic sequencing and long-term clinical follow-up are required to clarify the biological mechanisms, diagnostic criteria, and therapeutic implications of DEK-AFF2 fusion in sinonasal carcinomas.